MARGIN OF SAFETY OF HIRING DECISION OF AGRICULTURAL MACHINERY SERVICES BY RICE FARMERS IN ALNAJAF AL-ASHRAF PROVINCE - Kadhim, Z. R. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The main objective of this study is to compute margin of safety of hiring decision of agricultural machinery services in Iraq. A cost-volume-profit analysis by using breakeven point technique has been followed to find out the margin of safety by using cross- section data in rice production farms in Alnajaf province. Results showed that the break-even point for different types of original agricultural field machinery were 427, 6.5, and 221 hours for tractor and machinery of soil preparation, farm sprayer, and combine harvester, respectively, while the values of break-even point for different types of used agricultural field machinery were 309, 10, and 319 hours for tractor, farm sprayer, and combine harvester, in that order. Results also pointed out that the negative sign of safety margin of areas of all machineries indicated that there are losses faced by small scale farmers in case of ownership these machineries, and the minimum lose amounted about $ 316116 for original tractor, $ 52611 for used tractor, $ 220.5 for original farm sprayer, $ 88 for used farm sprayer, $ 664664 for original combine harvester and $ 584650 for used combine harvester. The study recommended that it is useful for small scale farmers in Alnajaf province to continue hiring various agricultural machinery services rather than purchase them due to the absence of safety margin of holding areas. Therefore machine stations of agricultural machineries services maybe developed by Iraqi government in the study region to provide these services to the farmers with supported prices.